Intercalated architecture of MA2Z4 family layered van der Waals materials with emerging topological, magnetic and superconducting properties - Wang, Lei; Shi, Yongpeng; Liu, Mingfeng; Zhang, Ao; Hong, Yi-Lun; Li, Ronghan; Gao, Qiang; Chen, Mingxing; Ren, Wencai; Cheng, Hui-Ming; Li, Yiyi; Chen, Xing-Qiu (Nature communications, 2021)
The search for new two-dimensional monolayers with diverse electronic properties has attracted growing interest in recent years. Here, we present an approach to construct MA 2 Z 4 monolayers with a septuple-atomic-layer structure, that is, intercalating a MoS 2 -type monolayer MZ 2 into an InSe-type monolayer A 2 Z 2 . We illustrate this unique strategy by means of first-principles calculations, which not only reproduce the structures of MoSi 2 N 4 and MnBi 2 Te 4 that were already experimentally synthesized, but also predict 72 compounds that are thermodynamically and dynamically stable. Such an intercalated architecture significantly reconstructs the band structures of the constituents MZ 2 and A 2 Z 2 , leading to diverse electronic properties for MA 2 Z 4 , which can be classified according to the total number of valence electrons. The systems with 32 and 34 valence electrons are mostly semiconductors. Whereas, those with 33 valence electrons can be nonmagnetic metals or ferromagnetic semiconductors. In particular, we find that, among the predicted compounds, (Ca,Sr)Ga 2 Te 4 are topologically nontrivial by both the standard density functional theory and hybrid functional calculations. While VSi 2 P 4 is a ferromagnetic semiconductor and TaSi 2 N 4 is a type-I Ising superconductor. Moreover, WSi 2 P 4 is a direct gap semiconductor with peculiar spin-valley properties, which are robust against interlayer interactions. Our study thus provides an effective way of designing septuple-atomic-layer MA 2 Z 4 with unusual electronic properties to draw immediate experimental interest. The discovery of a new two-dimensional van der Waals layered MoSi 2 N 4 material inspires many attentions. Here, the authors report intercalation strategies to explore a much wider range of MA 2 Z 4 family and predict amount of materials accessible to experimental verifications with emergent topological, magnetic or Ising superconductivity properties.